2018
DOI: 10.2139/ssrn.3233900
|View full text |Cite
|
Sign up to set email alerts
|

How Does Exposure to Mass Media Affect HIV Testing and HIV-Related Knowledge Among Adolescents? Evidence from Uganda

Abstract: Sexual and reproductive health remains one of the greatest challenges in developing countries. In Uganda, adolescents are the most vulnerable group as far as HIV epidemic is concerned. Mass media awareness campaigns play a key role in promoting sexual and reproductive health among adolescents. Using Uganda's 2016 Demographic Health Survey, we examine the causal effect of mass media exposure on the probability of adolescents getting an HIV test and their HIV-related knowledge. Our results suggest that the expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…These campaigns acted as catalysts to ART uptake and adherence since they inspired participants to accept themselves thus managing a number of limitations for example rejection, self-hatred, and stigma as well as spurring positive living. Our results are in agreement with a study done in Uganda about how exposure to mass Media affect HIV Testing and HIV-related knowledge among adolescents which found that Mass media awareness campaigns play a key role in promoting sexual and reproductive health among adolescents (15). Whereas these campaigns positively in uenced ART uptake among adolescents, our study participants expressed concerns about the languages these messages were frequently aired out.…”
Section: Discussionsupporting
confidence: 92%
“…These campaigns acted as catalysts to ART uptake and adherence since they inspired participants to accept themselves thus managing a number of limitations for example rejection, self-hatred, and stigma as well as spurring positive living. Our results are in agreement with a study done in Uganda about how exposure to mass Media affect HIV Testing and HIV-related knowledge among adolescents which found that Mass media awareness campaigns play a key role in promoting sexual and reproductive health among adolescents (15). Whereas these campaigns positively in uenced ART uptake among adolescents, our study participants expressed concerns about the languages these messages were frequently aired out.…”
Section: Discussionsupporting
confidence: 92%
“…The same study also suggested that continuous and proactive media movements may lead to diffusion of ideas that may ultimately promote HIV testing. Evidence from the analysis of the 2016 Uganda DHS and result from a longitudinal analysis conducted in India also showed that exposure to mass media was signi cantly associated with HIV related knowledge (33,35), and, from the current study, it is evident that HIV related knowledge is strongly associated with HIV VCT uptake.…”
Section: Discussionsupporting
confidence: 64%
“…This result is similar to the ndings from Zimbabwe and Burkina Faso where exposure to media was positively associated with HIV VCT uptake (21,29). Evidence from the analysis of the 2016 Uganda DHS showed that listening to radio once a week and watching television more than once a week increases the odds of being tested for HIV by 4.57% and 8.57% respectively (33). Another study in SSA using three rounds of DHSs also presented that there is a signi cant relationship between exposure to mass media and HIV VCT uptake (34).…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on previous studies on general media exposure (Donaldson et al, 2017;Lompo & Bago, 2018), we measured newspaper exposure with a single item on a 5-point scale using the question, "What is your frequency of reading newspaper reports on the political happenings in Nigeria?" Possible responses ranged from Never (1) to Always (5) (α = 0.81).…”
Section: Newspaper Exposurementioning
confidence: 99%